Uji Efektivitas Antidiabetik Kombinasi Ekstrak Daun Senggani (Melastomapolyanthum .Bl) dan Glibenklamid dalam Menurunkan Kadar Glukosa Darah pada Mencit (Mus Musculus): Antidiabetic Effectiveness Test of A Combination of Senggani (Melastoma Polyanthum .Bl) and Glibenclamide Leaf Extract in Reducing Blood Glucose Levels in Mice (Mus Musculus) - Sry Widyastuti; Samsidar Usman; Dina Rahayu (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
This study aims to determine the antidiabetic effectiveness of the combination of Senggani leaf extract (Malestoma polyanthum Bl.) And Glibenclamide against alloxan-induced mice. This study used 15 male mice divided into 5 groups and each group consisted of 3 male mice, group I was given Na.CMC 1% w / v, groups III, IV, V were each given a combination of senggani leaf extract 90 mg / kg, 180 mg / kg, 360 mg / kg and 5 mg of glibeclamide as the treatment group, and for group II were given glibenclamide suspension 5 mg for comparison. Alloxan 150 mg / KgBW was used as an inducer of diabetes. Measurement of blood glucose levels was carried out three times, namely initial glucose measurement, post-induction glucose measurement and post-treatment glucose measurement. The results showed that giving senggani leaf extract with a concentration of 90 mg / kg BW, 180 mg / kg BW, 360 mg / kg BW had an antidiabetic effect in male mice. Senggani leaf extract 360 mg / kg BW showed the most effective antidiabetic effect, but still more smaller than the 5 mg glibenclamide suspension.